Akad Maslahah Mursalah Dalam Transaksi Perbankan Di Agen BRILINK - Nurzidan, Yusup; Efendi, Mahmudin (Musyarokah: Jurnal Hukum dan Ekonomi Islam, 2023)
Bank services are bank service products provided to customers to meet their needs. Banks offer service products with the aim of providing services to bank customers or other parties who need them. At BRI Bank, there is a program called BRILink to support officeless services and bring people closer to banking services. This program is expected to provide convenience for people who cannot yet access financial services. Among the government-owned conventional banks that have joined the program is BRI. The aim of this research is to find out how banking transactions and Maslahah Murslah contracts are carried out on banking transactions at the BRILink Agent S2 Celluler shop, Sukaresmi Village, Kec. South Cikarang District. Bekasi. The research is descriptive qualitative in nature. The data sources used are primary and secondary data sources. Data collection was carried out using interview and documentation techniques. The resulting data is described descriptively and analyzed using inductive thinking. The research results obtained in this research are that the implementation of banking transactions by BRILink Agent banking transactions at the S2 Celluler Store runs quickly, safely and comfortably. BRILink Toko S2 CELL agents really help the people who live around Sukaresmi Village. All banking transactions can be carried out such as transfers between BRI, inter-bank transfers, prepaid and postpaid electricity payments, multi-finance payments, and Top Up top-ups. Keywords: Maslahah Murlahah Agreement, BRILINK Transaction